Pemodelan Matematis Besaran Pengaruh pada Kasus Keputusan Pembelian Konsumen Gerai Rumah Karawo - Abdussamad, Siti Nurmardia (Fakultas Pertanian, Universitas Timor, 2024)
The development of the business world has advanced very rapidly in the current era of globalization, where there is a lot of competition between companies that have the same business. One of the businesses that developed from the creations of children from the Gorontalo area is Karawo. Karawo is a symbol of Gorontalo's cultural identity, to this day not only has consumers in its own area but consumers outside the Gorontalo area. So it is important for companies to pay attention to attractiveness in terms of consumer purchasing decisions. Several factors that influence purchasing decisions include buyer awareness of a brand, product price and perceived quality. By using a mathematical model using a quantitative approach with a regression analysis method, it can describe whether there is an influence of brand awareness, price and perceived quality on consumer purchasing decisions at Gerai Rumah Karawo and the magnitude of the influence. The data collection technique was by distributing questionnaires to 68 respondents. The research results show that brand awareness, price and perceived quality simultaneously influence consumer purchasing decisions at the Rumah Karawo Outlet by 69.5%.